2011
DOI: 10.1093/jnci/djr325
|View full text |Cite|
|
Sign up to set email alerts
|

Sequential vs Concurrent Chemoradiation for Stage III Non-Small Cell Lung Cancer: Randomized Phase III Trial RTOG 9410

Abstract: Concurrent delivery of cisplatin-based chemotherapy with TRT confers a long-term survival benefit compared with the sequential delivery of these therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
768
6
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,084 publications
(832 citation statements)
references
References 20 publications
41
768
6
17
Order By: Relevance
“…The results showed that both concurrent CRT regimens increased median survival compared with that of sequential therapy and that 5-year survival was significantly increased from 10% in patients who received sequential CRT to 16% in patients treated with concurrent chemotherapy and once-daily RTX. Higher rates of acute toxicities were observed with the concurrent CRT regimens (8). Similar results were seen in another phase III trial comparing sequential and concurrent CRT in inoperable stage III NSCLC (9).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results showed that both concurrent CRT regimens increased median survival compared with that of sequential therapy and that 5-year survival was significantly increased from 10% in patients who received sequential CRT to 16% in patients treated with concurrent chemotherapy and once-daily RTX. Higher rates of acute toxicities were observed with the concurrent CRT regimens (8). Similar results were seen in another phase III trial comparing sequential and concurrent CRT in inoperable stage III NSCLC (9).…”
Section: Introductionsupporting
confidence: 78%
“…These earlier studies consisted of both sequential (1,2) and concurrent (3)(4)(5)(6) chemoradiotherapy (CRT) regimens, including daily (5, 6) and twice-daily hyperfractionated RTX (3,4), and sequential delivery of chemotherapy and thoracic RTX became a standard therapeutic approach in patients with inoperable stage III NSCLC (8). Although concurrent CRT regimens increased the frequency of severe hematologic and nonhematologic toxicities, the survival benefits were considered significant enough to conduct a phase III trial to determine which CRT regimen, concurrent or sequential, was more beneficial (8). This phase III study compared two different concurrent CRT treatment strategies, one with daily and one with twice-daily RTX, with an established sequential CRT regimen (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Phase III trials that have revealed a statistically significant longer OS with concurrent compared to sequential chemotherapy and radiation have used older chemotherapy combinations of mitomycin, vindesine, and cisplatin (MVP), cisplatin and vinblastine, or cisplatin and etoposide [5][6][7]. Many clinicians have adopted more recently developed chemotherapy agents based on the perception that these agents have lower toxicity and/or greater efficacy.…”
Section: Third-generation Chemotherapy Agentsmentioning
confidence: 99%
“…Both seminal trials that established concurrent therapy as the standard of care also suggested that the superior OS outcome was, in large part, a result of enhanced locoregional control. In the RTOG 94 -10 trial, the 2-year infield relapse rate was lower, 30% versus 39%, whereas the long-term intrathoracic tumor control rate was higher, 50% versus 35%, in the West Japan Lung Cancer Group Trial [5,6]. Therefore, it seems that strategies focused on further enhancing local tumor control may translate to meaningful improvements in OS outcomes.…”
Section: Trt Considerationsmentioning
confidence: 99%
“…The addition of chemotherapy concurrently increases efficacy of radiation for local control and has the added benefit of targeting micrometastatic disease. The use of concurrent radiotherapy with chemotherapy has improved response rates and survival over sequential chemoradiotherapy: There is a potential for cure even without surgery, with 5-year survival rates of approximately 15% to 20% (28)(29)(30). In otherwise healthy patients treated with induction chemoradiation, surgical resection may be beneficial if the primary tumor can be removed with a lobectomy.…”
Section: Systemic Chemotherapy In Curative Settingsmentioning
confidence: 99%